Mental Habits Behind Seeking Folk Healing in Rural Philippines - John Erwin Pedroso; Roy Rean Jen Siojo; John Michael Eugalca; Ariane Delmo; Miriya Bianca Delcano; Kristhel Dianne Jardeleza (Skad)
This study explored the mental habits of locals in a rural community in the Philippines regarding folk healing, with a particular focus on the use of herbs and food restrictions. Conducted in the first half of 2024, the research aimed to understand how these traditional healing practices persist and influence local perceptions of health and well-being. Data were gathered from ten (10) informants through in-depth interviews, guided by a validated semi-structured interview guide. The collected data were then analyzed using Clarke and Braun’s thematic analysis to identify recurring patterns in the participants’ responses. Two (2) main themes emerged from the analysis: (1) Integrating the Power of Herbs and Touch in Folk Healing, which highlights the widespread belief in the therapeutic effects of herbal remedies combined with physical touch; and (2) Adhering to Food Restrictions, which underscores the community’s practice of avoiding certain foods to aid in recovery or prevent illness. These findings suggest that folk healing remains deeply embedded in the community’s cultural and mental framework, reinforcing a shared reliance on traditional health practices.